Alloantibodies against the B subunit of plasma factor XIII developed in its congenital deficiency - Wada, Hideho; Souri, Masayoshi; Matsumoto, Rui; Sugihara, Takashi; Ichinose, Akitada (Thrombosis and Haemostasis, 2013)
Factor XIII (FXIII) is a fibrin-stabilising factor consisting of catalytic A subunits (FXIII-A) and carrier B subunits (FXIII-B). FXIII-B prevents the fast clearance of FXIII-A from the circulation. Congenital FXIII-A deficiency is a rare bleeding disorder, and congenital FXIII-B deficiency is even rarer. Through our recent nationwide survey on “acquired haemophilia-like disease due to anti-FXIII autoantibodies,” we newly diagnosed severe congenital FXIII-B deficiency in a Japanese man. He developed thrombocytopenia and gingival bleedings at the age of 73, and his FXIII activity was as low as 10% of the normal. When he suddenly developed spontaneous intramuscular haematoma, the bleeding was arrested by infusing FXIII concentrates. However, his FXIII activity remained around 10% of the normal. At the age of 74, ELISA and western blotting assay unexpectedly revealed complete absence of FXIII-B in the patient’s plasma. A dot blot assay detected anti-FXIII-B alloantibodies for the first time in this disease, which could be attributed to the infusion of exogenous FXIII. He was found to be homozygous for a Japanese founder-effect mutation of F13B. Repeated infusions of exogenous FXIII for hemostasis increased anti-FXIII-B alloantibodies that resisted FXIII substitution. To the best knowledge of the authors, none of the remaining 10 reported cases of congenital FXIII-B deficiency developed alloantibodies to exogenous FXIII-B of plasma FXIII. An originally mild bleeding phenotype of severe congenital FXIII-B deficiency can be exaggerated by additional acquired conditions. Physicians should consider congenital FXIII-B deficiency when they encounter cases of unexplained bleeding disorders.
Keywords: Factor concentrates; factor XIII/transglutaminases; inherited coagulation disorders; alloantibody; factor XIII-resistant state